Educational leadership, organizational learning, and the ideas of Karl Weick perspectives on theory and practice - Johnson, Bob L. 1956-; Kruse, Sharon D. (Routledge, Taylor & Francis Group, 2019)
Grounded in the theory of sociologist Karl Weick, this edited volume explores key concepts of educational leadership and organizational learning. Chapter authors analyze and reflect on the implications of Weick's thinking on leadership preparation and development. Providing a thorough understanding of the influence of his ideas in education, this volume unpacks the ways in which Weick's ideas influence and shape organizational learning and educational leadership and policy today